2008
DOI: 10.1063/1.2906362
|View full text |Cite
|
Sign up to set email alerts
|

Floating electrode optoelectronic tweezers: Light-driven dielectrophoretic droplet manipulation in electrically insulating oil medium

Abstract: We report an optical actuation mechanism, floating electrode optoelectronic tweezers ͑FEOET͒. FEOET enables light-driven transport of aqueous droplets immersed in electrically insulating oil on a featureless photoconductive glass layer with direct optical images. We demonstrate that a 681 m de-ionized water droplet immersed in corn oil medium is actuated by a 3.21 W laser beam with an average intensity as low as 4.08 W / mm 2 at a maximum speed of 85.1 m / s on a FEOET device. FEOET provides a promising platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…Park's group achieved droplet manipulation in oil using a sandwiched OET platform integrated with microfluidic channels and showed the manipulation of picoliter droplets by optically induced DEP forces [63]. Park et al have recently demonstrated a mechanism, called floating electrode optoelectronic tweezers (FEOET), specifically aiming for manipulating aqueous droplets suspended in electrically insulating oil and air media ( Figure 9) [64]. FEOET utilizes lateral electric field as in SCOEW.…”
Section: Optoelectronic Tweezers (Oet)mentioning
confidence: 99%
“…Park's group achieved droplet manipulation in oil using a sandwiched OET platform integrated with microfluidic channels and showed the manipulation of picoliter droplets by optically induced DEP forces [63]. Park et al have recently demonstrated a mechanism, called floating electrode optoelectronic tweezers (FEOET), specifically aiming for manipulating aqueous droplets suspended in electrically insulating oil and air media ( Figure 9) [64]. FEOET utilizes lateral electric field as in SCOEW.…”
Section: Optoelectronic Tweezers (Oet)mentioning
confidence: 99%
“…In order to solve this problem, a threedimensional (3D) OEK chip consisting of two parallel photosensitive layers was designed to set up a symmetrical spatial electric field and focus the object in the middle of the liquid layer [70]. A single-sided ODEP device was also developed to enable manipulation based on a modulation of lateral electric field generated by the interdigitated electrodes patterned on a single-side substrate [61] or a floating electrode [65,71].…”
Section: Q4mentioning
confidence: 99%
“…Similar to the concept of OET, floating electrode optoelectronic tweezers (FEOET) explores another frequency regime for aqueous droplet manipulation 103,104 ( Fig. 9d).…”
Section: Floating Electrode Optoelectronic Tweezers (Feoet)mentioning
confidence: 99%
“…9d). Park et al 103,104 showed that a target object as large as a nano-litre droplet in a two-phase environment, such as water in oil, can be driven by a light-induced dipole moment. The electric field is created by a DC bias on two far separated electrodes.…”
Section: Floating Electrode Optoelectronic Tweezers (Feoet)mentioning
confidence: 99%